E-Service Quality on the Ubud Monkey Forest Website, Gianyar (Demand Perspectives) - Dwiari, Ni Made Septi; Mahadewi, Ni Made Eka; Mertha, I Wayan (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
This study aims to determine the e-service quality on the Monkey Forest Ubud website, Gianyar with a tourist perception approach. The sampling technique used was non-probability sampling with a total of 192 respondents consisting of domestic and foreign tourists. The analysis technique used in this study was measured using Importance Performance Analysis (IPA). The results of the study show that the level of satisfaction of domestic and foreign tourists has different satisfactions. Domestic tourists have a 92% suitability rate and foreign tourists have a 90% suitability rate. Based on the GAP analysis, it was found that the average was (-0.30) which means that tourists are still not satisfied with the service that meets the expectations of tourists. The findings of this study can be used as a consideration to improve the quality of electronic services by prioritizing indicators that have low performance with high levels of tourist expectations.